Persekutuan Yang Holistik: Tinjauan Dogmatis Tentang Hakikat Gereja dari Perspektif Konfessi HKBP - Harianja, Mikael; Hasibuan, Ricky Pramono (JURNAL DIAKONIA, 2023)
This article discusses the importance of the concept of Holistic Fellowship in understanding the essence of the Church, with a comparison to the HKBP Confession. The author emphasizes that fellowship in the current church life must be holistic, involving both spiritual and physical aspects, and not limited to individual worship. The research method used is literature review. The author asserts that Holistic Fellowship involves the participation of church members in all aspects of life, including their relationship with God and fellow human beings, in order to serve in social and other areas. The author also reviews the concept of fellowship in the HKBP Confession, which emphasizes a holistic understanding of fellowship in theological aspects.